2012
DOI: 10.1111/rda.12021
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression in Pre‐Term, Pre‐Labour and Parturient Canine Placenta

Abstract: Contents Matrix metalloproteinases (MMPs), tissue inhibitors of metalloproteinases (TIMPs), vascular endothelial growth factor (VEGF)‐A, VEGF‐A receptor (Flt‐1) and KiSS‐1 receptor (KiSS‐1R) all play a role in trophoblast invasion in a number of mammalian species. However, mRNA expression of factors regulating trophoblast invasion has not been studied in dogs. Abnormal expression of these factors at the end of canine gestation may contribute to placental retention and/or subinvolution of placental sites. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…The first evidence confirming the role of kisspeptin-54 in the regulation of invasion processes by MMPs, a family of Zn- and Ca 2+ —dependent endopeptidases, has been presented by Yoshioka et al on the in vitro model of renal carcinoma cells [ 92 ]. This observation has been confirmed by other studies, which strongly indicated that kisspeptin decreased trophoblast cells’ invasion by attenuation of MMPs expression dose-dependent [ 9 , 28 , 93 ]. Francis et al demonstrated that kisspeptin-10 treatment reduced the expression of MMP-2 in the primary trophoblast cells and subsequently disturbed their migratory capability [ 46 ].…”
Section: Role Of Kisspeptin In the Pathogenesis Of Disorders From The...supporting
confidence: 83%
“…The first evidence confirming the role of kisspeptin-54 in the regulation of invasion processes by MMPs, a family of Zn- and Ca 2+ —dependent endopeptidases, has been presented by Yoshioka et al on the in vitro model of renal carcinoma cells [ 92 ]. This observation has been confirmed by other studies, which strongly indicated that kisspeptin decreased trophoblast cells’ invasion by attenuation of MMPs expression dose-dependent [ 9 , 28 , 93 ]. Francis et al demonstrated that kisspeptin-10 treatment reduced the expression of MMP-2 in the primary trophoblast cells and subsequently disturbed their migratory capability [ 46 ].…”
Section: Role Of Kisspeptin In the Pathogenesis Of Disorders From The...supporting
confidence: 83%
“…An overview of the current knowledge regarding the distribution and gestational expression patterns of some of the extracellular matrix related factors in the dog can be found under [11,26,51,52]. The canine trophoblast has an invasive character.…”
Section: Utero-placental Extracellular Matrix During Canine Placentationmentioning
confidence: 99%
“…invasion) into maternal structures does not stop, and strong invasion of the trophoblast at the bottom of the placental labyrinth is observed until term. Interestingly, whereas major matrix metalloproteinases (MMP2 and -9) are expressed in fetal trophoblast cells [51,52], their inhibitors, in particular TIMP2, are expressed in both counterparts of the placenta (i.e. in the placenta materna and placenta fetalis) [26], including the fetal trophoblast, implying a possible self-regulatory feedback loop protecting the maternal compartments from excessive trophoblast invasion [26].…”
Section: Utero-placental Extracellular Matrix During Canine Placentationmentioning
confidence: 99%